An Assessment of Transformational Leadership of School Heads and Its Relationship to the School Climate - Santos, Orlando R.; Caparas, Laurenne Anne R.; Medina, Arnold B.; Cabrera, Wendell C. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
Attaining high levels of learning outcomes has been the core of school management, operations, and teaching. Correspondingly, various programs, projects, and activities of the Department of Education (DepEd) aimed toward the recovery and enhancement of learning, and ultimately the holistic development of the youth have been implemented every academic year. Some of the key factors for pupils' learning and holistic development are the provision of a positive school climate and the leadership style of the school heads. Hence, this review paper looked into the existing literature for the given key variables and identified the research gap and future research perspectives. The findings showed that there is a significant relationship between idealized influence, inspirational motivation, and personal consideration. As assessed in all the domains of transformational practices of school heads as highly observed, meanwhile, intellectual stimulation does not significantly influence the school climate thus, much effort is required from the school heads to inspire and motivate the teachers to attain higher performance of the students. This paper hopes to contribute to the potential research undertakings in the locale and provide clarity about how transformational leadership impacts school climate which ultimately leads to positive learning outcomes.